Sigmoid volvulus after laparoscopic surgery for sigmoid colon cancer. Issue 3 (24th July 2013) - Sadatomo, Ai; Miyakura, Yasuyuki; Zuiki, Toru; Koinuma, Koji; Horie, Hisanaga; Lefor, Alan T; Yasuda, Yoshikazu
Abstract We report the first case of sigmoid volvulus after laparoscopic surgery for sigmoid colon cancer. The patient is a 75‐year‐old man who presented with the sudden onset of severe abdominal pain. He had undergone laparoscopic sigmoidectomy for cancer 2 years before presentation. CT scan showed a distended sigmoid colon with a mesenteric twist, or "whirl sign." Colonoscopy showed a mucosal spiral and luminal stenosis with dilated sigmoid colon distally and ischemic mucosa. The diagnosis of ischemic colonic necrosis due to sigmoid volvulus was established. Resection of the necrotic sigmoid colon was performed and a descending colon stoma was created. A long remnant sigmoid colon and chronic constipation may contribute to the development of sigmoid volvulus after laparoscopic sigmoidectomy. Prompt diagnosis is essential for adequate treatment, and colonoscopy aids in the diagnosis of ischemic changes in patients without definitive findings of a gangrenous colon.